Biosysthesis of Corn Starch Palmitate by Lipase Novozym 435 - Kai Lin; Le Chang; Chun-Gu Xia; Yan Wang; Tie Liu; Jia-Ying Xin (International Journal of Molecular Sciences, 2012)
Esterification of starch was carried out to expand the usefulness of starch for a myriad of industrial applications. Lipase B from Candida antarctica , immobilized on macroporous acrylic resin (Novozym 435), was used for starch esterification in two reaction systems: micro-solvent system and solvent-free system. The esterification of corn starch with palmitic acid in the solvent-free system and micro-solvent system gave a degree of substitution (DS) of 1.04 and 0.0072 respectively. Esterification of corn starch with palmitic acid was confirmed by UV spectroscopy and IR spectroscopy. The results of emulsifying property analysis showed that the starch palmitate with higher DS contributes to the higher emulsifying property (67.6%) and emulsion stability (79.6%) than the native starch (5.3% and 3.9%). Modified starch obtained by esterification that possesses emulsifying properties and has long chain fatty acids, like palmitic acid, has been widely used in the food, pharmaceutical and biomedical applications industries.